2018
DOI: 10.5539/gjhs.v10n7p11
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Prevalence, Awareness, Treatment and Control among Adults in Malaysia: The 2015 National Health and Morbidity Survey, Malaysia

Abstract: Background & Objective: Dyslipidaemia is one of the main modifiable risk factors for cardiovascular disease (CVD). Therefore, it is crucial to examine the prevalence, awareness, treatment and control of hypercholesterolemia and its associated factors among adults in Malaysia. Methods:We used data from 19,935 respondents aged 18 years and above who responded to the cholesterol module in the National Health and Morbidity Survey (NHMS) 2015. The survey employed a two-stage stratified sampling to select a represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Inversely, several sociodemographic characteristics, such as ethnicity and the availability of health insurance had been found to be negatively associated with the use of LLM [13,14]. In Malaysia, the prevalence of LLM use among individuals with hypercholesterolemia was previously reported [15], however its use among high CVD risk population has yet to be explored. Thus, the aim of this study was to determine the prevalence of LLM use for primary and secondary prevention of CVD among Malaysian adults, and the factors associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…Inversely, several sociodemographic characteristics, such as ethnicity and the availability of health insurance had been found to be negatively associated with the use of LLM [13,14]. In Malaysia, the prevalence of LLM use among individuals with hypercholesterolemia was previously reported [15], however its use among high CVD risk population has yet to be explored. Thus, the aim of this study was to determine the prevalence of LLM use for primary and secondary prevention of CVD among Malaysian adults, and the factors associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia, which is an alteration of any lipid components in the blood, is one of the major risk factors of IHD. It was reported that the prevalence of hypercholesterolemia in Malaysia was 47.7% in 2015 [ 3 ]. Hypercholesterolemia leads to the development of atherosclerosis and CHD that can be detected by coronary angiogram or coronary calcium score (CT scan).…”
Section: Introductionmentioning
confidence: 99%
“…Several types of commonly known diseases have been determined to be related to hereditary gene mutations. In developed or developing countries including Malaysia, the major well-known non-communicable health concerns include hypertension, diabetes, and hypercholesterolemia (Lim et al, 2004 ; Hussein et al, 2015 ; Naing et al, 2016 ; Tee and Yap, 2017 ; Rifin et al, 2018 ). On the other hand, ~5–10% of cancers are known to contain hereditary components (Lu et al, 2014 ; Stanislaw et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%